The Irony Approach in the Qur'an: Mustansir Mir's Perspective - Azam Azam (AJIS: Academic Journal of Islamic Studies, 2020)
In the Qur’an interpretation, the irony approach is hardly ever used by commentators. Muntasir Mir is one of the commentators who used the irony approach in analyzing the. This paper then aims to explain Mir’s thoughts in his article entitled “Irony in the Qur’an: a Study of the Story of Joseph. “In this article,heinterpreted the Qur’an by using the irony approach thatintroduced a new discourse to interpret the Qur’an for Muslims. Besides, Miraims to showthat theunderstanding of the Qur’an is not only stagnant in theological understanding. He invites Muslims to possess the beauty of literature contained in the Qur’an. Furthermore, Mir tried to illustrate the irony in the story of the Prophet Joseph. He described irony as an event beyond logic since it is a message fromGod. The Irony of the Prophet Joseph is a representation of humans’ lousy plan that Allah changed to be good. It described the ambitious efforts of his brothers to destroy him by sending him to a well, but conversely, it took him to the peak of fame and power. And all the efforts to alienate the Prophet Joseph finally comes at His mercy